Intraoperative Neurophysiologic Examination in Central Nervous System Tumor Surgery: Four-year Single-institution Experience - F Gökçem Yıldız (Türk Nöroloji Dergisi, 2017)
Objective: Intraoperative neurophysiologic monitoring (IONM) is widely used nowadays to minimize neurologic morbidity in neurosurgical operations. Our goal was to describe the standard IONM techniques used in our center and to discuss our own clinical experience with a multimodality approach. Materials and Methods: All consecutive adult patients consulted for neurosurgical operations who underwent at least one modality of IONM (brainstem-evoked potential, motor-evoked potential, somatosensory-evoked potential, and/or electromyography) were retrospectively reviewed. Results: Twenty-eight patients who underwent central nervous system tumor surgery between 2012 and 2016 received IONM. IONM minimizes the neurologic morbidity of surgery and allows identification and differentiation of functional neural tissues. Conclusion: Multimodal IONM is a valuable tool for optimization of outcomes in complex central nervous system surgery